DECOMMISSIONING OF OFFSHORE PLATFORMS - Kurian, V.J.; Ganapathy, C. (Construction Industry Research Achievement International Conference 2009, CREAM, CIDB Malaysia, 2009)
In the development of offshore platforms, many jacket platforms were constructed in the seventies both in continental shelf and in deepwater of depths around 300m. As the service life of these platforms was about thirty years, at present, the decommissioning of several platforms are being planned and executed. Offshore platform decommissioning is a challenge in terms of planning and executing the work in an environmentally sensitive, safe and economical way. This is particularly true in the context of large deepwater platforms. While a number of new technologies are being developed, a review of these methods is appropriate and this paper discusses the decommissioning methods. The decommissioning starts with the removal of conductors, subsea systems and topsides followed by the installation process in reverse sequence. Each module is removed and placed on a cargo barge and towed to different locations depending on the planning for subsequent use. The usual methods of decommissioning are; Complete Removal, Partial Removal and Remote Reefing. It may be stated that the Partial Removal scenario, combined with conventional heavy lift vessels, severing and subsea technologies, is currently the safest and most cost-effective technique. Evaluation of cost sensitivity issues and the cost of alternative technologies are discussed in this paper. The environmental effects on the marine aquatic life due to explosive method and alternative methods of diamond cutting system, abrasive water jet cutting system, diver cutting system etc. are also reviewed. A novel and new method of decommissioning is also presented and discussed.